Genome of the African cassava whitefly Bemisia tabaci and distribution and genetic diversity of cassava-colonizing whiteflies in Africa - Chen, W.; Wosula, Everlyne N.; Hasegawa, D.K.; Casinga, C.; Shirima, R.R.; Fiaboe, K.K.M.; Hanna, R.; Fosto, A.; Goergen, Georg E.; Tamò, Manuele; Mahuku, George S.; Murithi, H.M.; et al. (Elsevier, 2019)
The whitefy Bemisia tabaci, a species complex consisting of many morphologically indistinguishable species divided into distinct clades, is one of the most globally important agricultural pests and plant virus vectors. Cassava-colonizing B. tabaci transmits viruses that cause cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). Half of all cassava plants in Africa are affected by these viral diseases, resulting in annual production losses of more than US$ 1 billion. Here we report the draft genome of the cassava whitefly B. tabaci Sub-Saharan Africa - East and Central Africa (SSA-ECA), the super-abundant population that has been associated with the rapid spread of viruses causing the pandemics of CMD and CBSD. The SSA-ECA genome assembled from Illumina short reads has a total size of 513.7 Mb and a scaffold N50 length of 497 kb, and contains 15,084 predicted protein-coding genes. Phylogenetic analysis suggests that SSA-ECA diverged from MEAM1 around 5.26 million years ago. A comprehensive genetic analysis of cassava-colonizing B. tabaci in Africa was also conducted, in which a total of 243 whitefly specimens were collected from 18 countries representing all major cassava-growing regions in the continent and genotyped using NextRAD sequencing. Population genomic analyses confirmed the existence of six major populations linked by gene flow and inferred the distribution patterns of these populations across the African continent. The genome of SSA-ECA and the genetic findings provide valuable resources and guidance to facilitate whitefly research and the development of strategies to control cassava viral diseases spread by whiteflies.